Liberating the Mind: Overcoming Sociocentric Thought and Egocentric Tendencies - Elder, Linda (Rowman & Littlefield Publishers, 2019)
Throughout history, thinkers within every part of society have been crippled by an ingrained bias toward their own views and the views of their preferred social groups. As these dangerous egocentric and sociocentric tendencies continue to pose the greatest threat to the advancement of rational societies, Liberating the Mind reveals a way forward. Dissecting the core of how humans naturally learn, think, and choose to act, internationally recognized critical thinking leader Linda Elder illuminates root causes of dysfunctional thought andshows us how to free ourselves from both selfishness and groupthink through explicit tools of rationality. This instant intellectual classic offers a cohesive, integrated theory of mind that takes into account pathological tendencies shared by all humans, while offering a clear path toward the cultivation of fairminded critical thinking throughout the world. Elder illuminates how, by taking the intrinsic problems in our thinking seriously, we can follow the example of Socrates and live the examined life, even in times of upheaval and doubt.